1998
DOI: 10.1038/sj.bmt.1701384
|View full text |Cite
|
Sign up to set email alerts
|

CD34+-enriched donor lymphocyte infusions in a case of pure red cell aplasia and late graft failure after major ABO-incompatible bone marrow transplantation

Abstract: Summary:A variety of immunohematological complications may occur after ABO-incompatible BMT. We report a CML patient (blood group O) who received a BMT from an HLA-identical sibling (blood group AB). The transplant was followed by normal myeloid and megakaryocytic engraftment, but erythroblastopenia persisted for more than 200 days after BMT. By bone marrow culture studies, a complement-dependent serum inhibitor of hemopoiesis was detected, suggesting immunological inhibition of erythropoiesis. The patient was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…2,4,54 Other reports have documented resolution of PRCA after DLI. 55,56 In our study, discontinuation of CsA appeared sufficient to induce a graft-mediated immune effect against host cells involved in isohemagglutinin production, leading to resolution of PRCA. While such immune-based strategies appear effective, GHVD may also ensue.…”
Section: Discussionmentioning
confidence: 96%
“…2,4,54 Other reports have documented resolution of PRCA after DLI. 55,56 In our study, discontinuation of CsA appeared sufficient to induce a graft-mediated immune effect against host cells involved in isohemagglutinin production, leading to resolution of PRCA. While such immune-based strategies appear effective, GHVD may also ensue.…”
Section: Discussionmentioning
confidence: 96%
“…Other investigators have reported stem cell boosts, 28 DLI, 29 or CD34 þ -enriched DLI 30 as an effective therapy for declining donor chimerism, poor graft function, or mixed chimerism. Anti-T cell therapy with ATG and CAMPATH proved ineffective at stabilizing mixed chimerism in patient 2.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil engraftment was reached after 17 days (95%-CI [16][17][18][19] and platelet engraftment after 32 days (95%-CI 27-38) without differences between the groups (p=0.379 and p=0.364, respectively). As shown in Figure 1B, patients who underwent anti-donor isoagglutinin reduction had faster RBC engraftment (p<0.001).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%